Nanoparticles on electric, gas, and diesel buses in mass transit buses of Bogotá Colombia - Diego Armando Vargas; Boris Galvis; Vanesa Durán; Ivan Camilo Bernal (TeMA: Journal of Land Use, Mobility and Environment, 2023)
The concentration of traffic-related air pollutants (TRAP) within transport microenvironments has become increasingly relevant in many megacities with high population density, intense traffic, and prolonged travel times. These conditions can intensify exposure to TRAP and exacerbate public health problems. However, TRAP concentrations in these microenvironments are changing due to the introduction of cleaner technologies. In this study, we compared the concentration of nanoparticles inside diesel, gas, and electric buses during their normal operation in Bogota, Colombia. We used a miniature diffusion size classifier (DiSCmini) to measure the nanoparticles' concentrations, average particle size, and lung-deposited surface area. Our results revealed significantly lower levels of this pollutant inside electric buses. Specifically, the concentration of nanoparticles per cubic centimeter was approximately 41% and 27% lower in electric buses compared to diesel and gas buses, respectively. Additionally, the lung-deposited surface area was also lower in electric buses. However, the average particle size in electric buses was 10% and 18% smaller compared to diesel and gas buses, respectively. The results of this study give useful information for future selection processes of bus technologies for public passenger transport in cities around the world; This research provides information that can be used in technical evaluation processes that link the possible health effects on commuters and impacts the environment.